Therapeutic Effects of Customized ORA Heal Mouthwash on Oral Lichen Planus Patients Reporting at Oral Medicine Clinic at Tertiary Care Hospital - Salima Naveed Manji, Hina Ali, Khizer Mehmood, Muzzamil Ahmad, Nasir Ali Choudhry, Maria Noor, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the therapeutic effects of Customized Ora Heal mouthwash on oral lichen planus patients reporting at oral medicine clinic at tertiary care hospital. Study Design: Descriptive Cross-sectional study Place and Duration of Study: Department of Oral Medicine, from June-Dec 2022. Methodology: This is a descriptive cross-sectional study in which a survey based on the visual analog scale (VAS) was planned and conducted on sixty patients reported to oral medicine department of Dental Hospital reporting with Lichen Planus. Results: The study included sixty participants, of which 31 (51.6%) were male and 29 (48.3%) female reporting at Oral medicine department of Dental hospital. The mean age of participants was 45.15. Pre-VAS of participants shows a mean score of 5.033 (moderate pain). After a follow-up of 2 weeks interval, post-VAS of participants shows a mean score of 2.231 (mild pain). Conclusion: The study shows a decreasing trend in pain intensity of the participants using Ora Heal mouthwash based on pre VAS and post VAS score. Keywords: Lichen Planus; Ora Heal; Mouthwash; Corticosteroids; VAS score; Pathogenesis; Autoimmune disorder; Mucocutaneous